Improving the quality of life of patients with inflammatory skin diseases: a multicenter evaluation of a ceramide-containing regimen in patients with atopic dermatitis, psoriasis and xerosis - Carlota Abbad-Jaime de Aragon; Emilio Berna-Rico; Leonor Prieto; Mercedes Abarquero-Cerezo; Álvaro Gonzalez-Cantero (Journal of Dermatological Treatment)
Purpose Atopic dermatitis (AD), psoriasis and xerosis are characterized by alterations in the skin barrier leading to symptoms that severely impair patients’ quality of life (QoL). This multicenter, prospective study evaluated the benefits of a 4-week ceramide-containing regimen on the symptoms and QoL of patients with AD, psoriasis, or xerosis.Materials and methods Clinical assessments (SCORAD, PASI, VAS), QoL and adherence to the treatment were evaluated at baseline and after 4 weeks.Results A total of 312 patients (109 AD, 97 psoriasis and 106 xerosis) participated in the study; 59.3% female, mean age 42.4 years, no family history of AD, psoriasis or xerosis in ∼70% of patients. Significant clinical improvements after 4 weeks were reported: 61.2% reduction in SCORAD in AD; 65.5% reduction in PASI in psoriasis; and reductions in VAS for dryness, erythema and other symptoms in xerosis patients. QoL improved in all groups (67.2% AD, 64.7% psoriasis, 77.3% xerosis), with a significant proportion of patients reducing their concomitant treatments. Most patients adhered to the regimen, and no adverse reactions were reported.Conclusions A ceramide-containing regimen reduced the symptoms commonly associated with AD, psoriasis, and xerosis and improves patients’ QoL. Limitations include the lack of control group and limiting conclusions about ceramides’ contribution on effectiveness.